Antarctic marine geology - Anderson, John B. 1944- (Cambridge University Press, 1999)
The fragile Antarctic environment consists of a closely linked system of the lithosphere, atmosphere, cryosphere, hydrosphere and biosphere. Changes in this system have influenced global climate, oceanography and sea level for most of Cenozoic time. The geological history of this region therefore provides a special record of important interactions between the various components of the Earth System. Antarctic Marine Geology is a comprehensive single-authored book to introduce students and researchers to the geological history of the region and the unique processes that occur there. Research literature on the region is widely disseminated. The book is intended as a reference for all scientists working in Antarctica, and will also serve as a textbook for graduate courses in Antarctic marine geology.